Whole genome amplification from a single cell: implications for genetic analysis. - Zhang, L (1992)
We have developed an in vitro method for amplifying a large fraction of the DNA sequences present in a single haploid cell by repeated primer extensions using a mixture of 15-base random oligonucleotides. We studied 12 genetic loci and estimate that the probability of amplifying any sequence in the genome to a minimum of 30 copies is not less than 0.78 (95% confidence). Whole genome amplification beginning with a single cell, or other samples with very small amounts of DNA, has significant implications for multipoint mapping by sperm or oocyte typing and possibly for genetic disease diagnosis, forensics, and the analysis of ancient DNA samples.